Disability, social functioning and school inclusion among older children and adolescents living with HIV in Zimbabwe. Issue 2 (26th December 2017) - Rukuni, Ruramayi; McHugh, Grace; Majonga, Edith; Kranzer, Katharina; Mujuru, Hilda; Munyati, Shungu; Nathoo, Kusum; Gregson, Celia L.; Kuper, Hannah; Ferrand, Rashida A.
Abstract: Objective: Increasing numbers of children with HIV are surviving to adolescence and encountering multiple clinical and social consequences of long‐standing HIV infection. We aimed to investigate the association between HIV and disability, social functioning and school inclusion among 6‐ to 16‐year‐olds in Zimbabwe. Methods: HIV‐infected children receiving antiretroviral therapy from a public‐sector HIV clinic and HIV‐uninfected children attending primary care clinics in the same catchment area were recruited. Standardised questionnaires were used to collect socio‐demographic, social functioning and disability data. Multivariable logistic regression was used to assess the relationship between HIV status and disability and functioning. Results: We recruited 202 HIV‐infected and 285 HIV‐uninfected children. There was no difference in age and gender between the two groups, but a higher proportion of HIV‐infected children were orphaned. The prevalence of any disability was higher in HIV‐infected than uninfected children (37.6% vs . 18.5%, P < 0.001). HIV‐infected children were more likely to report anxiety (adjusted odds ratio (aOR) 4.4; 95% CI 2.4, 8.1), low mood (aOR 4.2; 2.1, 8.4) and difficulty forming friendships (aOR 14.8; 1.9, 116.6) than uninfected children. Children with HIV also reported more missed school days, repeating a school year and social exclusion in class. These associations remained apparent when comparing children with HIV and disability to those with HIV but no disabilities. Conclusions: Children with HIV commonly experience disabilities, and this is associated with social and educational exclusion. Rehabilitation and support services are needed to facilitate educational attainment and social participation in this group.